Influence of agricultural practices on biotic production potential and climate regulation potential: a case study for life cycle assessment of soybean (Glycine max) in Argentina - Piastrellini, Roxana (2015)
The aim of this study is to determine the impact potential of land use on biotic production and climate regulation in the agricultural phase of a product, taking into account the varied soil and crop management. Land occupation and transformation impacts of soybean production in Argentina for different agricultural systems are evaluated. The results indicate that the magnitude of occupation and transformation impacts is considerably reduced by implementing no-tillage instead of conventional tillage. Nevertheless, the methodologies adopted are unable to show any of the expected differences between rainfed or irrigation systems, crop sequences and delays in seed-planting, due to failures in the specific characterization factors. On the other hand, an uncertainty is demonstrated by the results associated with the choice of regeneration time corresponding to the different ecoregions over which soybean cultivation extends across the country. One of the recommendations that comes to the fore is to consider in the characterization factors increments in the soil organic carbon stock and in the mineralization rates, associated with the presence of the preceding crop and the greater availability of water in the soil of irrigated systems.